Genome-wide analysis of dysregulated RNA-binding proteins and alternative splicing genes in keloid - Zhu, Zhen; Ni, Shuangying; Zhang, Jiali; Yuan, Ying; Bai, Yun; Yin, Xueli; Zhu, Zhengwei (Frontiers in Genetics, 2023)
The pathogenesis of keloids remains unclear. In this study, we analyzed RNA-Seq data (GSE113619) of the local skin tissue of 8 keloid-prone individuals (KPI) and 6 healthy controls (HC) before and 42 days after trauma from the GEO database. The differential alternative splicing (AS) events associated with trauma healing between KPI and HC were identified, and their functional differences were analyzed by GO and KEGG pathways. The co-expression relationship of differentially AS genes and differentially expressed RBPs was established subsequently. A total of 674 differential AS events between the KD42 and the KD0 and 378 differential AS events between the HD42 and the HD0 were discovered. Notably, most of the differential genes related to keloids are enriched in actin, microtubule cells, and cortical actin cytoskeletal tissue pathway. We observed a significant association between AS genes (EPB41, TPM1, NF2, PARD3) and trauma healing in KPI and HC. We also found that the differential expression of HC-specific trauma healing-related RBPs (TKT, FDPS, SAMHD1) may affect the response of HC to trauma healing by regulating the AS of downstream trauma healing-related genes such as DCN and DST. In contrast, KPI also has specific differential expression of trauma healing-related RBPs (S100A9, HspB1, LIMA1, FBL), which may affect the healing response of KPI to trauma by regulating the AS of downstream trauma healing-related genes such as FN1 and TPM1. Our results were innovative in revealing early wound healing-related genes (EPB41, TPM1, NF2, PARD3) in KPI from the perspective of AS regulated by RBP.